Cultural Differences of Needed Qualities towards Entrepreneurship - Treacy, Stephen; Brandt, Tiina; Al-Kharusi, Sami; Bakhadirov, Mukhammadfoik; Ahmed, Gouher; Militaru, Andreea Maria Gabriela; Bakker, Diederich; Dubickis, Mikus (Journal of Entrepreneurship, Business and Economics; Vol 12 No 2 (2024), 2025)
This paper explores the link between culture and tailored entrepreneurial education, addressing how cultural differences, influenced by Hofstede's dimensions, impact entrepreneurial behaviour. The study involves 772 students from higher education institutions in the Asian, Baltic, and Eastern European regions, utilizing factor analyses and statistical methods to identify entrepreneurial qualities from Likert-scale evaluations of 13 items. Findings reveal notable regional differences, highlighting traits like courage in Japan and China, and risk-taking in the USA. This research underscores the need for context-sensitive strategies in entrepreneurship education, advocating for tailored support to overcome cultural barriers. Ultimately, it enriches understanding of how culture shapes entrepreneurial behaviour and informs strategies for multinational corporations and education curricula. Research Paper Keywords: Entrepreneurial Intentions, Cultural Differences, Entrepreneurial Qualities Reference to this paper should be made as follows: Treacy, S., Brandt, T., Al-Kharusi, S., Bakhadirov, M., Ahmed, G., Militaru, A.M.G., Bakker, D., & Dubickis, M. (2024). Cultural Differences of Needed Qualities towards Entrepreneurship. Journal of Entrepreneurship, Business and Economics , 12 (2), 69–108.